2019
DOI: 10.1063/1.5112033
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and dynamics of erythrocytes govern their traversal through microfluidic devices with a deterministic lateral displacement architecture

Abstract: Deterministic lateral displacement (DLD) microfluidic devices promise versatile and precise processing of biological samples. However, this prospect has been realized so far only for rigid spherical particles and remains limited for biological cells due to the complexity of cell dynamics and deformation in microfluidic flow. We employ mesoscopic hydrodynamics simulations of red blood cells (RBC) in DLD devices with circular posts to better understand the interplay between cell behavior in complex microfluidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Chien et al 77 reported modeling studies of a DLD device that employed mesoscopic hydrodynamics of RBCs in DLD devices with circular posts to better understand the interplay between cell behavior in complex microfluidic flow environments and sorting capabilities of such devices. The authors identified regimes of RBC dynamics (e.g., tumbling, tank-treading, and trilobe motion) and presented mode diagrams of RBC behavior (e.g., displacement, zig-zagging, and intermediate modes) while residing in the DLD device.…”
Section: Deterministic Lateral Displacement and Density Gradient Centrifugation Cell Sortingmentioning
confidence: 99%
“…Chien et al 77 reported modeling studies of a DLD device that employed mesoscopic hydrodynamics of RBCs in DLD devices with circular posts to better understand the interplay between cell behavior in complex microfluidic flow environments and sorting capabilities of such devices. The authors identified regimes of RBC dynamics (e.g., tumbling, tank-treading, and trilobe motion) and presented mode diagrams of RBC behavior (e.g., displacement, zig-zagging, and intermediate modes) while residing in the DLD device.…”
Section: Deterministic Lateral Displacement and Density Gradient Centrifugation Cell Sortingmentioning
confidence: 99%
“…Various numerical methods have been used so far to characterize the flow and particle behavior in DLD microsystems. A distinction can be made between calculations of the steady-state flow field [14,[17][18][19][20][21] and simulations that include particle dynamics [8,15,[22][23][24][25][26][27][28][29][30][31][32][33][34]. The calculation of the velocity field only allows for an estimation of the behavior of particles in the flow and the d c , but the interactions between particles and the fluid are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of the velocity field only allows for an estimation of the behavior of particles in the flow and the d c , but the interactions between particles and the fluid are neglected. The fluid-structure interactions are either calculated in direct numerical simulations (DNS) [25][26][27][28][29]32] or the fluid and solid phases are calculated in separate processes, and both methods are coupled iteratively; for example, the lattice Boltzmann method (LBM) coupled with the discrete element method (LBM-DEM) [30] or coupled with the finite element method (FEM) [31]. The fluid-structure simulations were either simplified into two dimensions [8,15,[22][23][24]28,32,34,35] or calculated in a more complex three-dimensional way [25][26][27][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations